The Effect Of Seed Treatment Duration With Entomopathogenic Fungi Beauveria Bassiana On Seed Germination And Seedling Growth Of Chili - Trizelia Trizelia (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
Beauveria bassiana (Balsamo) Vuill. is an entomopathogenic fungi can live endophytic on different kinds of plants. B. bassiana also play a role as growth promoters that improves seed germination and growth of plant. The effect of increased duration of seed treatment with Beauveria bassiana on seed germination and seedling parameters in chili were assessed in laboratory and field conditions. Chili seeds were soaked in the conidial suspension of B. bassiana in a concentration of 1 x 108 conidial / ml or in sterile distilled water for 3, 6, 9, and 12 h. Seed germination percentages and the vigor index were significantly affected by the application of B. bassiana. Overall, seed germination, the vigor index and plant growth of chili were significantly enhanced as seed treatment duration increased. B. bassiana can also accelerate seed germination of chili and increase of seedling growth. Soaking the seeds with a B. bassiana suspension for 9 hours is the best time to increase of seed germination and seedling growth of chili